Effects of Health Insurance on Perceived Quality of Care Among Latinos in the United States - Perez, Debra (Springer-Verlag, 2009)
BACKGROUND: There is suggestive evidence that lower rates of health insurance coverage increases the gaps in quality and access to care among Latinos as compared with non-Latino whites. In order to examine these potential disparities, we assessed the effects of insurance coverage and multiple covariates on perceived quality of care. OBJECTIVE: To assess the distribution of perceived quality of care received in a national Latino population sample, and the role of insurance in different patient subgroups. DESIGN: Telephone interviews conducted between 2007 and 2008 using the Pew Hispanic Center/Robert Wood Johnson Foundation Latino Health Surveys (Waves 1 and 2). PARTICIPANTS: Randomly selected Latino adults aged ≥18 years living in the United States. MEASUREMENTS: Pearson χ(2) tests identified associations among various demographic variables by quality of care ratings (poor, fair, good, excellent) for the insured and uninsured (Wave 1: N = 3545). Subgroup analyses were conducted among Wave 2 participants reporting chronic conditions (N = 1067). Bivariate and multivariate analyses were conducted to estimate the effects of insurance, demographic variables and consumer characteristics on quality of care. RESULTS: Insurance availability had an odds ratio of 1.47 (95% CI, 1.22–1.76) net of confounders in predicting perceived quality of care among Latinos. The largest gap in rates of excellent/good ratings occurred among the insured with eight or more doctor visits compared to the uninsured (76.2% vs. 54.6%, P < .05). CONCLUSIONS: Future research can gain additional insights by examining the impact of health insurance on processes of care with a refined focus on specific transactions between consumers and providers’ support staff and physicians guided by the principles of patient-centered care.